Antithrombotics in Heart Failure With Reduced Ejection Fraction and Normal Sinus Rhythm: An Evidence Appraisal. (February 2014) - Prom, Rathasen; Usedom, James E.; Dull, Ryan B.
Objective: To review the thromboembolic risk, pathophysiology associated with the risk, and literature investigating the use of antithrombotics in patients with heart failure with reduced ejection fraction and normal sinus rhythm (HFrEF-NSR).Data Sources: An English language literature search was performed with MEDLINE/PubMed and Embase from January 1950 to October 2013 using the search terms heart failure, HFrEF, systolic heart failure, cardiomyopathy, left ventricular dysfunction, sinus rhythm, thromboembolism, deep vein thrombosis, pulmonary embolism, myocardial infarction, acute coronary syndrome, acute coronary events, coronary artery disease, stroke, and cerebrovascular events to identify relevant articles. References in the retrieved articles were also assessed to identify other important articles.Study Selection and Data Abstraction: All pertinent original studies, reviews, consensus documents, and guidelines were evaluated for inclusion.Data Synthesis: Patients with HFrEF-NSR may be predisposed to developing thromboembolic events. Studies that have examined the role of antithrombotics (warfarin and/or antiplatelet therapy) for reducing thromboembolic risk have been inconclusive. The WASH and HELAS pilot trials—the only studies with a no-antithrombotics or placebo comparator group—did not find a benefit with antithrombotic therapy but found an increased risk of bleeding with warfarin and of hospitalizations with aspirin. Although the clinical outcome studies (WATCH and WARCEF) suggested that warfarin may reduce stroke risk compared with antiplatelet therapy, the lack of a placebo group and lower-than-projected enrollment prevents definitive conclusions from being made.Conclusions: Current evidence does not support the routine use of antithrombotics for preventing thromboembolic events in patients with HFrEF-NSR without compelling indications.